Numerical research of biomechanical system with SMA prosthesis - Mitura Andrzej; Rusinek Rafal (MATEC Web of Conferences, 2018)
In this paper the modelling of special biomechanical mechanism and application of shape memory materials are presented. The model of the human middle ear is made as multibody system. The basic 3dof ear model of the healthy middle ear is modified to represent the damaged ear. A damaged of the ossicular chainis taken into account by adding gap in visco-elastic joints. In addition, an attempt of the ossicles chain reconstruction through prosthesis made of shape memory alloy is presented. Moreover, a new description of the hysteresis sub-loop which characterise prosthesis material is proposed. Finally, dynamic responses of healthy, damaged and reconstructed models of the middle ear are compared by quality index.